Technical assessment of electric heat boosters in low-temperature district heating based on combined heat and power analysis. (1st May 2018) - Cai, Hanmin; You, Shi; Wang, Jiawei; Bindner, Henrik W.; Klyapovskiy, Sergey
Abstract: This paper provides a technical assessment of electric heat boosters (EHBs) in low-energy districts. The analysis is based on a hypothetical district with 23 terraced single-family houses supplied by both a low-temperature district heating (LTDH) network and a low-voltage network (LVN). Two case studies are provided to show the active role of EHBs in a smart energy system (SES). The first case compares annual heat and power flow analyses for LTDH at five supply temperature levels, focusing on their impacts. The results show that district heating network (DHN) losses can be reduced by 35% if the supply temperature is reduced from 70 °C to 50 °C, but the LVN peak power will have to be increased by up to 2% using heat boosting. The second case further aggregates EHBs to provide a fuel shift (FS) service for the DHN. The results show that while LVN peak power was increased by up to 4.3%, the basic power production and peak boiler usage for DHN could be reduced by as much as 15% and 48%, respectively. In summary, lower supply temperatures and intelligent components can improve system efficiency and turn the DHN into an integrated part of a SES. Highlights: Comprehensive model of heat and power network flow for steady-state simulation. Analysis of the performance of a low-energy district in 5-min intervals. Detailed electric heat booster model and controller design in a real-world context. Design of fuel shift service for the district heating sector to optimize operation. Analysis of the advantages of lower supply temperatures and smart components.